Cumulative ecological risk and problematic smartphone use among Chinese college students: the roles of performance goal orientation, learning goal orientation and psychological resilience - Guan, Jinliang; Yu, Peng; Liu, Chengzhen; Ma, Wangyan (Frontiers in Psychology, 2024)
Problematic smartphone use (PSU) has emerged as a pressing concern among college students, with cumulative ecological risk identified as a crucial yet enigmatic contributor. To unravel its underlying mechanisms, we devised and validated a model that delves into the mediating roles of performance and learning goal orientations, as well as the moderating influence of psychological resilience. Our investigation encompassed 2011 Chinese college students spanning from freshmen to seniors, aged 16 to 25, utilizing comprehensive scales to assess various constructs. The findings revealed that both performance and learning goal orientations serve as pivotal mediators in the relationship between cumulative ecological risk and PSU. Furthermore, psychological resilience was found to moderate not only the direct link between cumulative ecological risk and PSU but also the indirect pathway through learning goal orientation. These insights underscore the practical significance of fostering healthy achievement goals and enhancing psychological resilience among college students, thereby mitigating the prevalence of PSU.